The selfless act - Brunstetter, Wanda E.; Brunstetter, Jean (Brunstetter, Wanda E. Amish millionaire, 2016)
Businessman Joel Byler who has gotten himself into a financial bind and his eccentric, wealthy Amish father who is done bailing out his spoiled son. When will Joel learn he most pay for his own mistakes and at what cost to his business, his fiancée, and his Amish siblings?